Pertussis seroprevalence among adults of reproductive age (20–39 years) in fourteen European countries. Issue 9 (1st July 2021) - Wehlin, Lena; Ljungman, Margaretha; Kühlmann‐Berenzon, Sharon; Galanis, Ilias; Huygen, Kris; Pierard, Denis; Dalby, Tine; Petridou, Evi; Molnár, Zsuzsanna; Carollo, Maria; Ausiello, Clara M.; Lipnickiene, Vilnele; et al.
Abstract: The reported incidence of pertussis in European countries varies considerably. We aimed to study specific Bordetella pertussis seroprevalence in Europe by measuring serum IgG antibody levels to pertussis toxin (anti‐PT IgG). Fourteen national laboratories participated in this study including Belgium, Denmark, Finland, Greece, Hungary, Italy, Lithuania, Malta, Norway, Poland, Portugal, Romania, Spain, and Sweden. Each country collected approximately 250 samples (N = 7903) from the age groups 20–29 years (N = 3976) and 30–39 years (N = 3927) during 2010–2013. Samples were anonymous residual sera from diagnostic laboratories and were analyzed at the national laboratories by a Swedish reference method, a commercial ELISA kit, or were sent to Sweden for analysis. The median anti‐PT IgG concentrations ranged from 4 to 13.6 IU/mL. The proportion of samples with anti‐PT IgG ≥100 IU/mL, indicating a recent infection ranged from 0.2% (Hungary) to 5.7% (Portugal). The highest proportion of sera with anti‐PT IgG levels between 50 and <100 IU/mL, indicating an infection within the last few years, was found in Portugal (12.3%) and Italy (13.9%). This study shows that the circulation of B. pertussis is quite extensive in adults, aged 20–39 years, despite well‐established vaccination programs in Europe.